2019
DOI: 10.15244/pjoes/94809
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Cadmium, Lead and Mercury in Raw Bovine, Ovine, Caprine, Buffalo and Camel Milk

Abstract: Toxic heavy metals and especially lead (Pb), cadmium (Cd) and mercury (Hg) can easily transmit to humans through consumption of contaminated milk. The present research was done to study the concentrations of Pb, Cd and Hg in different types of milk samples. In total, 1100 bovine, ovine, caprine, buffalo and camel raw milk samples were collected in different regions of Iran and analyzed to determine concentrations of Pb, Cd and Hg by a graphite furnace atomic absorption spectrometric method. The mean recoveries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
4
2
Order By: Relevance
“…In the milk samples of shops, the maximum concentration of Pb was found in July (216.9 ± 0.810 mg/L), followed by October (24.11 ± 6.687 mg/L) and August (14.00 ± 4.041 mg/L), and the lowest was observed in June (3.600 ± 1.610 mg/L). The measured levels of Pb in the present study were comparatively higher than those reported earlier in Italy [ 48 ], Egypt [ 49 , 50 ], Azerbaijan [ 51 ], and Iran [ 53 , 54 ]. Lead can affect all organs/systems in the human body, especially the central nervous system [ 64 ] and may cause death by interfering with the cardiovascular system [ 65 ].…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…In the milk samples of shops, the maximum concentration of Pb was found in July (216.9 ± 0.810 mg/L), followed by October (24.11 ± 6.687 mg/L) and August (14.00 ± 4.041 mg/L), and the lowest was observed in June (3.600 ± 1.610 mg/L). The measured levels of Pb in the present study were comparatively higher than those reported earlier in Italy [ 48 ], Egypt [ 49 , 50 ], Azerbaijan [ 51 ], and Iran [ 53 , 54 ]. Lead can affect all organs/systems in the human body, especially the central nervous system [ 64 ] and may cause death by interfering with the cardiovascular system [ 65 ].…”
Section: Resultscontrasting
confidence: 88%
“…The measured levels of Cd in buffalo milk collected from homes and shops of different localities in Abbottabad were relatively higher than the previously reported levels in the same type of milk from Italy [ 48 ], Egypt [ 49 , 50 ], Azerbaijan [ 51 ], and Pakistan [ 52 ]. However, in the present study, the average concentration of Cd was less than the reported levels in buffalo milk from Iran [ 53 , 54 , 55 ].…”
Section: Resultscontrasting
confidence: 85%
“…In another study, a high value of lead (30 μg/L) was observed again, whereas 2 μg/L of cadmium was lower than the acceptable limit (5 μg/L) ( 15 ). More recently, heavy metals have been detected in camel milk in Nigeria ( 16 , 17 ), Iran ( 18 ), Kenya ( 19 ), and Pakistan ( 20 ).…”
Section: The Camel Milk a “Natural Product”?mentioning
confidence: 99%
“…Heavy metal contamination in soil has become a severe issue around the world in recent years as a result of anthropogenic activities [1,2]. Cd is recognized as one of the most toxic and carcinogenic metals in soil, which may transfer from plants to human body by dietary intake exposure [3][4][5]. Various techniques were available to remediate the heavy metal-polluted soil.…”
Section: Introductionmentioning
confidence: 99%